TELAAH NILAI-NILAI PANCASILA DALAM PEMBENTUKAN KARAKTER BANGSA DI ERA DIGITAL - Mimin Ninawati; Amelia Nabilla Zahra; Dina Trisia; Najwa Laika Putri Abdi; Niken Widy Astuti; Fathiyah Rachmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to examine how Pancasila values ​​have shaped Indonesian society in the digital era. The main issue raised is how Pancasila can function as a moral and ethical basis to overcome the difficulties faced by the younger generation as a result of the influence of digital technology. This study uses a literature review methodology combined with a qualitative research strategy, utilizing secondary data from various related scientific articles and journals. To synthesize knowledge based on the author's ideas and experiences, the analysis process is carried out narratively. The findings of the study indicate that the basic values ​​of Pancasila. Divinity, Humanity, Unity, Democracy, and Social Justice can function as a framework for developing strong social ethics. In the context of education, the incorporation of Pancasila values ​​into the curriculum makes a significant contribution to the development of a young generation that has strong digital ethics and academic intelligence. This study also emphasizes how important it is for the government, education community, and society to work together in order to promote the implementation of Pancasila values ​​in all areas of life, including online. The younger generation is expected to be able to respond to the complexity of the digital era wisely, ethically, and with integrity if Pancasila values ​​are prioritized